Cost optimal analysis of lighting retrofit scenarios in educational buildings in Italy. (September 2017) - Bonomolo, Marina; Baglivo, Cristina; Bianco, Giacomo; Maria Congedo, Paolo; Beccali, Marco
Abstract: The European Energy Performance of Buildings Directive (EPBD) recast proposes, a comparative methodology to calculate cost-optimal levels of minimum energy performance requirements for buildings. This paper presents a method able to select the best retrofit action for lighting system, selectively analysing the daylight conditions and applying the cost-optimal methodology for different scenarios proposed for two existing educational buildings located in Italy. With the aim to improve both energy efficient and visual comfort conditions, the retrofit scenarios include lighting solutions with different combinations. They consider the replacement of lamps with more efficient lighting sources and the application of lighting control.